Achilles insertional tendinopathy: state of the art. Issue 1 (21st October 2018) - Maffulli, Nicola; Saxena, Amol; Wagner, Emilio; Torre, Guglielmo
Abstract : Achilles tendon pathology is a most common musculoskeletal condition in active individuals and athletes. Almost 6% of the general population will suffer from such ailment in their lifetime. Insertional Achilles tendinopathy (IAT) differs in its physiopathology, clinical features and treatment from midportion tendinopathy. The literature has mainly focused on assessment, outcome evaluation and treatment of IAT, although differences in management according to different geographical regions have not been addressed. The principles of clinical evaluation and imaging assessment of IAT are well established, with a major role of clinical assessment and soft tissue imaging, including ultrasonography and MRI. Conservative management options include eccentric training, extracorporeal shockwave therapy and prolotherapy, or a combination of these modalities. Recently, regenerative medicine has been more widely used, with at times dubious results. Surgery is advocated where conservative treatment is not beneficial within 6 months. Surgery includes more or less extensive debridement of peritendinous bony and soft tissue structures. To improve our knowledge about IAT, more evidence should be provided concerning innovative treatments, especially considering growth factors injections and percutaneous surgery.